Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2018)
The 60th number of the Cuadernos de Administración journal is the first one of 2018, a year in which we are consolidating this means of scientific dissemination, with the entry into several databases, the consolidation of our Editorial and Scientific committees and the process of internationalization of this publishing effort, which has promoted the dissemination of knowledge in Administration sciences throughout 42 years. On this occasion, the first paper entitled "Citizen participation through ICTs in the design of public policy in Colombia", presents the research results of a completed project, using data from 2013 and 2014, collected through surveys and interviews, to actors from different sectors in the department of Tolima, to assess the digitization strategy of the public sector. Opportunity strategies related to business competitiveness in restaurants in Mexico. Case: microenterprises in the municipality of Othón Payo. Blanco, Quintana Roo", is the second paper in this volume, wherein Mexican researchers analyze the relationship between organizational management and the business competitiveness of microenterprises in the restaurant sector in the municipality of Othón Payo Blanco, Quintana Roo. Among their main findings, they obtain that the business competitiveness in this region of Mexico is oriented towards technology and organizational culture, where strategic alliances are one of the strategies for achieving competitiveness within the sector. The third article is entitled "Quality Analysis of hotels service in Medellín through perceptual maps", is the result of a research wherefrom the perception of national and international guests staying in different hotels in Medellín, registered in the platform TripAdvisor, 57 hotels between 2005 and 2010 show that the factors most valued by guests are cleanliness, quality of rest and service above the location, price and comfort of the rooms, among others. "Sectorial adjustment costs induced by the Colombian pattern of international trade, 1991-2015", is the title of the fourth paper, wherein the authors analyze the adjustment costs induced by the Colombian international trade pattern for the 1991-2015 period; they calculate marginal intra-industrial trade indexes, adjustment costs and the use of the International Adjustment Cost Space and present different types of results. The fifth article, entitled "Craftsmanship and champeta: cultural industries and local development in the municipalities of Clemencia and María la Baja in the department of Bolívar", seeks to highlight the production process of cultural goods and services within the champeta manifestations and handicrafts in the municipalities of Clemencia and María la Baja in the department of Bolívar, where they are able to demonstrate local capacities for the creative production of goods. Finally, "Multi-business companies: The Leonisa case" is the name of the sixth paper in this volume, which presents the study of the joint management of multi-business companies, in an exploratory manner in the case study of the company Leonisa, a Colombian multi-business company in the textile sector. Among the relevant findings are the company not having a corporate center (CC) with a formal structure, but a multi-divisional structure from which to manage the business as a whole. It is important to remember that the content of each of these six papers is their authors' absolute liability and does not compromise the Universidad del Valle, nor the Faculty of Administration Sciences, and their dissemination is carried out for academic purposes, as a contribution to the scientific development of the area and to encourage debate on each of these issues. We thank each of the authors, the professional work of the referees who accompanied us in this issue, and especially you, our readers, for thinking of this means of dissemination as an option for consultation in the academic work you do. We hope to have publications from all members of this extended scientific community that we are trying to build and consolidate.